2019
DOI: 10.12998/wjcc.v7.i22.3792
|View full text |Cite
|
Sign up to set email alerts
|

Sagliker syndrome: A case report of a rare manifestation of uncontrolled secondary hyperparathyroidism in chronic renal failure

Abstract: BACKGROUNDSagliker syndrome (SS) resulting from uncontrolled secondary hyperparathyroidism (SHPT) in chronic renal failure (CRF) is seldom reported.CASE SUMMARYA 24-year-old woman presented with asymmetric facial deformity and stature shortening. She was diagnosed with SS, SHPT, CRF, and thyroid cancer. The patient underwent a total parathyroidectomy and thyroidectomy with central lymph node dissection. The patient’s condition was stable and was discharged from the hospital.CONCLUSIONUndergoing dialysis vintag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…Laboratory values that are dominant in this syndrome are high serum PTH and ALP. High PTH (2815.07 pg/mL) and ALP (2350 U/L) with lower range of calcium (2.31 mmol/L) were presented for the patient in the case report done by Yu Yu et al in China 5 . Moreover, similar laboratory results were given in the research done by A. M. Pineda et al 7 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Laboratory values that are dominant in this syndrome are high serum PTH and ALP. High PTH (2815.07 pg/mL) and ALP (2350 U/L) with lower range of calcium (2.31 mmol/L) were presented for the patient in the case report done by Yu Yu et al in China 5 . Moreover, similar laboratory results were given in the research done by A. M. Pineda et al 7 .…”
Section: Discussionmentioning
confidence: 88%
“…Cholakova et al explains that commensurate increased serum alkaline phosphatase is responsible for this type of skeletal changes 4 . Yu Yu et al hypothesized that intramembranous ossification is hyperactivated in this syndrome, which then leads to thickening of the maxilla, anterior mandible and skull 5 . Moreover, in the international research of Yahya Sagliker et al they concluded that the GNAS1 gene missense mutations, which are possibly activated during the hemodialysis, might be responsible for genesis of SS 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Los hallazgos clínicos, bioquímicos, estudios de imagen e histopatológicos son las principales herramientas para establecer el diagnóstico de tumores pardos en el HPTS en individuos con síndrome de Sagliker 5,9 . Los niveles séricos de calcio, fósforo, fosfatasa alcalina y hormona paratiroidea en la evaluación inicial son de importancia para el manejo adecuado 13 . Así mismo, los estudios de imágenes permiten identificar alteraciones óseas no solo en los maxilares, sino también en otras áreas anatómicas 13 .…”
Section: Discussionunclassified
“…Los niveles séricos de calcio, fósforo, fosfatasa alcalina y hormona paratiroidea en la evaluación inicial son de importancia para el manejo adecuado 13 . Así mismo, los estudios de imágenes permiten identificar alteraciones óseas no solo en los maxilares, sino también en otras áreas anatómicas 13 . En el síndrome de Sagliker es frecuente observar lesiones con aspecto de sal y pimienta en los huesos craneales 8 .…”
Section: Discussionunclassified
“…Brown tumors secondary to hyperparathyroidism can also occur in the mandible and though typically asymmetric and focal along the mandible as opposed to diffuse as seen in uremic leontiasis ossea, they too will often have this alternating pattern of lucency and sclerosis which is indicative of rapid osteoclastic bone turnover and repair thought to result in this marbled appearance. [ 5 , 6 ]…”
Section: Discussionmentioning
confidence: 99%